1998
DOI: 10.1002/(sici)1097-0215(19980911)77:6<833::aid-ijc6>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of pericentromeric DNA in breast adenocarcinomas

Abstract: Drug‐induced DNA demethylation in normal human cells and inherited localized hypomethylation in mitogen‐stimulated lymphocytes from patients with a rare recessive disease (ICF: i―mmunodeficiency, c―entromeric region instability, f―acial anomalies) are associated with karyotypic instability. This chromosomal recombination is targeted to heterochromatin in the vicinity of the centromere (pericentromeric region) of human chromosome 1. Pericentromeric rearrangements in this chromosome as well as overall genomic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
137
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(152 citation statements)
references
References 17 publications
11
137
1
3
Order By: Relevance
“…Global DNA hypomethylation is thought to occur during the early stages of tumour development in gastric and other tissues (Goelz et al, 1985;Narayan et al, 1998;Lin et al, 2001;Bariol et al, 2003). Additionally, in pulmonary carcinogenesis, demethylation of the promoter CpG islands of MAGE genes has been observed not only in tumours but also in the adjacent non-neoplastic lung tissues and bronchial epithelia from smokers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global DNA hypomethylation is thought to occur during the early stages of tumour development in gastric and other tissues (Goelz et al, 1985;Narayan et al, 1998;Lin et al, 2001;Bariol et al, 2003). Additionally, in pulmonary carcinogenesis, demethylation of the promoter CpG islands of MAGE genes has been observed not only in tumours but also in the adjacent non-neoplastic lung tissues and bronchial epithelia from smokers .…”
Section: Discussionmentioning
confidence: 99%
“…Global DNA hypomethylation has been observed in carcinomas of the breast, liver, and colon, and is considered to occur in the early stages of tumour development (Goelz et al, 1985;Cravo et al, 1996;Narayan et al, 1998;Lin et al, 2001;Bariol et al, 2003). However, little is known about promoter hypomethylation of specific genes such as oncogenes and growth-related genes, with the exception of the association between demethylation and increased expression of c-abl, c-myc, Ha-ras, and raf (Cheah et al, 1984;Weitzman et al, 1989;Sharrad et al, 1992;Counts and Goodman, 1994).…”
mentioning
confidence: 99%
“…19 Two g of DNA were digested in 20 U of CpG methylsensitive restriction enzyme BstBI (New England Biolabs, Beverly, MA) for 16 hours. Complete DNA digestion was indicated with the aid of an internal DNA control, HindIII.…”
Section: Heterochromatin Hypomethylation By Southern Blot Analysismentioning
confidence: 99%
“…8,9 By Southern blot analysis with a CpG methylation-sensitive restriction endonuclease, we have shown that satellite 2 DNA (Sat2), the main sequence in the long juxtacentromeric (centromere-adjacent) heterochromatin of chromosome 1 (Chr1), is often hypomethylated in breast adenocarcinomas and Wilms tumors as well as in ovarian epithelial carcinomas. [10][11][12] Hypomethylation of this satellite DNA at 1qh was strongly linked to hypomethylation of the highly homologous satellite DNA at 16qh (Chrl6 Sat2) in these three disparate types of cancer. Also, in human hepatocellular carcinomas, hypomethylation of Sat2 was highly concordant with that of Sat3, the main DNA component of the long juxtacentromeric heterochromatin of Chr9.…”
Section: Introductionmentioning
confidence: 99%